A theological critique of Vattimo’s religious thought - Aramburu Zudaire, Mikel (Razón y fe, 2020)
Based on the main theses on the Christian religion of the Italian philosopher Gianni Vattimo, the article aims to give continuity to an earlier one by the author on the subject by summarizing various criticisms of some Catholic theologians and intellectuals (Girard, Borghesi, Dotolo, Mardones and Estrada). These point out certain limits and objections to Vattimo’s religious approach which they consider does not fit in its integrity within the correct doctrine of the Church, which postulates a “stronger” message and practice, although always from the kenotic style and disposition of the evangelical Jesus, which is what Vattimo primarily advocates.
Keywords: Gianni Vattimo; Christianity; weak thought; Catholic theology; kenosis; secularization